STRATEGI PENGELOLAAN PEMBIAYAAN SEKOLAH: STUDI KUALITATIF KOMPARATIF ANTARA SEKOLAH KOTA DAN DESA DI INDONESIA - Kisbudiono Kisbudiono; Joko Priyono; Sutrisno Sutrisno (STKIP Pesisir Selatan, 2026)
Education financing is a crucial element for the sustainability, quality, and equity of educational services. This study aims to explore and compare the strategies employed by schools in managing financing limitations, contrasting those located in urban settings with those in rural areas. Employing a qualitative approach with a comparative case study design, this research involved four schools: two in urban areas and two in rural areas. Data were collected through in-depth interviews with principals and treasurers, observations, and document analysis. The findings reveal a stark contrast in financing structures. Urban schools exhibit diversified funding sources, including community contributions, alumni donations, and private sector partnerships, coupled with advanced technological integration in financial management. In contrast, rural schools demonstrate a high dependency on government funding, primarily the School Operational Assistance (BOS) fund, with community participation playing a vital role in supplementing limited resources. The findings have significant theoretical implications for resource disparity theory and practical implications for developing context-specific financing policies, enhancing managerial capacity, and strengthening support for rural schools to foster more equitable educational outcomes.